Sustainable Development versus Irrational Exploitation of Romanian Forests - MEGHIȘAN, Flaviu (Journal of Advanced Research in Economics and International Business; Vol 3 No 4 (2015): JAREIB, Volume III, Issue 4, 2015, 2015)
Compared to the limited character and the uniqueness of the world, the strong economic and population growth, especially in southern countries, the companies and human economy must move from a way of growing which remained until now mainly extensive, to new economic ways of development, more just, more responsible and more solidary. This paradigm shift is a real stake of civilization. It undertakes to ask ourselves questions on the sustainability of the current growth model, instead and to build and promote a genuinely sustainable development, a concept formalized in 1987 by means of Brundltland Report in preparing the Rio Conference (1992), on a worldwide scale. Context? Increasing global economy exerts too much pressure on the Earth's resources. ‘Sustainable development’ implies a triple dimension: the economic development, the social equity and the intergenerational equity. Sustainable development strategies are different, just like the needs and priorities diverge in developed countries. Multinational corporations are not only exploiting millions of workers, but they also have a total control over natural resources in most developing countries that represent a huge source of natural resources, including Romania - fertile land, oil and gas, wood, copper, gold, and rare earth metals, etc. In this context, the policies of governments derive from the ideological orientation of political forces and the government, because of external pressures exerted on them and because of the economic situation of the moment. The forests represent a strategic national wealth. There is a direct relationship between the reserves held by the country and the nation's wealth or power of influence worldwide.